Extracting Slicer Parameters from STL file in 3D Printing - Patil, Sonali; Deshpande, Yogesh; Parle, Dattatraya (International Journal of Intelligent Systems and Applications in Engineering, 2024)
These 3D printing revolutionizes manufacturing by requiring accurate control and optimization of print parameters. Slicer software simplifies 3D modelling for printers by breaking down models into layer-wise instructions, calculates toolpath, generates support structures, aids in infill density, pattern control, and sets print settings. It includes a 3D preview and uses G-code, a 3D printing language, for printer setup. Extracting slicer parameters from G-code is crucial for quality control, documentation, optimization, troubleshooting, and educational purposes. The feature allows users to review settings and parameters during the slicing process, improving quality control, facilitating troubleshooting, identifying improvement areas, reducing print times, and enhancing material efficiency. Analysing slicer parameters in G-code can offer valuable insights into the printing process, enabling fine-tuning of print settings for enhanced quality and efficiency. This research paper reviews the challenges and techniques of extracting slicer parameters like G-code Parsing Algorithms, Regular Expression Matching, Metadata Extraction and Machine Learning Approaches. A novel method is discussed to extract the features by parsing the sliced STL file. The dataset generated can be further used to find Layer Thickness, Layer Height Distribution, Surface Quality, Interlayer Adhesion, Slice Alignment, Defect Detection and Geometric Analysis.